PENGARUH KEMUDAHAN BERTRANSAKSI dan SIFAT HEDONISME TERHADAP PERILAKU KONSUMTIF MAHASISWA EKONOMI SYARIAH ANGKATAN 2023 UNIVERSITAS SULTAN AGENG TIRTAYASA - Al-Wafa, Muhammad Qhodavi; Rohmah, Latifah Nur; Maida, Nadira Zelia; Fayza Kusumaputri, Laura Aurellia (Diponegoro Journal of Islamic Economics and Business, 2024)
The study assesses the influence of easier trade and the hedonism on the concustive behavior of students of the 2023 islamic economy university sultan ageng tirtayasa. The research method used in this study is a quantitative study method. In this study the authors use the primary type of data, that is, the data gained from angket distribution through Google form. The data comes from the online distribution of questionnaires through social media instagram and whatsapp. The research questionnaires use a likert scale with scale format provided in 1 to 5 options, with a gradations of very rarely, rarely, sometimes often, and very often. The population in this study is students of the 2023 islamic economy at sultan ageng tirtayasa university. The number of samples taken in this study USES the solvin formula to a minimum of 81 respondents. In this research the technique used to attract samples using the simple random sampling technique. The findings aim to provide insight into how easier transactions and the nature of hedonism contribute to the student spending habits, providing valuable information for educational institutions and policymakers to develop better financial education programs. Studies suggest that there is a positive effect between convenient transactions of consumer behavior is verified by a partial correlation that shows the significance of 0,000 < 0.05 and at value of t 11,986 > -0.572.Keywords: Ease of Transactions, Hedonistic Nature, Consumptive Behavior, Sharia Economics Students